Directional solidification of Zn–Al–Cu eutectic alloy by the vertical Bridgman method - Büyük, Uğur; ENGİN, Sevda and MARAŞLI, Necmettin (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
In the present work, the effect of growth rate and temperature gradient on microstructure and mechanical properties of Zn–7wt.%Al–4wt.%Cu eutectic alloy has been investigated. Alloys prepared under steady-state conditions by vacuumed hot filing furnace. Then, the alloys were directionally solidified upward with different growth rates (V=11.62–230.77 mm/s) at a constant temperature gradient (G=7.17 K/mm) and with different temperature gradients (G=7.17–11.04 K/mm) at a constant growth rate (V=11.62 mm/s) by a Bridgman furnace. The microstructures were observed to be lamellae of Zn, Al and broken lamellae CuZn4 phases from quenched samples. The values of eutectic spacing, microhardness and ultimate tensile strength of alloys were measured. The dependency of the microstructure and mechanical properties on growth rate and temperature gradient were investigated using regression analysis.